Does sports and physical education (Olympic value based) contribute to peace in Afghanistan? - Khawar, Jawid (Πανεπιστήμιο Πελοποννήσου, 2020)
Throughout the history, sports have been a strong and positive influence in people’s life style and social development. Considering the Ancient Olympic Truce all the way to the recent incidents; power of sport in Being a fantastic showcase for the peaceful rivalry between nations through sports competitions and building a friendship environment over conflicted and war-torn countries. The purpose of this study is to research and study “Does Sports and Physical education (Olympic Value Based) contribute to peace in Afghanistan?” In order to fulfill this purpose a quantitative approach was employed using questionnaires for Physical Education teachers at school, sport managers and a general questionary to public including the national team’s athletes and none-sportive personalities. This research is also a tool to understand the Physical Education teacher’s knowledge of Olympic and sports values, and their different approaches for teaching sports at school subject.
Keywords: Olympic education - Curriculum - Afghanistan; Physical education and training - Study and teaching (Elementary) - Afghanistan; Physical education and training - Research - Methodology - Afghanistan; Olympism; Ολυμπιακή παιδεία - Πρόγραμμα μαθημάτων - Αφγανιστάν; Φυσική αγωγή και εκπαίδευση - Μελέτη και διδασκαλία (Πρωτοβάθμια) - Αφγανιστάν; Φυσική αγωγή και εκπαίδευση - Έρευνα - Μεθοδολογία; Ολυμπισμός; Olympic education; Value based physical education; Afghanistan; Peace through sports